Patients’ and family members’ views on how clinicians enact and how they should enact incident disclosure: the “100 patient stories” qualitative study - Iedema, Rick (BMJ Publishing Group Ltd., 2011)
Objectives To investigate patients’ and family members’ perceptions and experiences of disclosure of healthcare incidents and to derive principles of effective disclosure. Design Retrospective qualitative study based on 100 semi-structured, in depth interviews with patients and family members. Setting Nationwide multisite survey across Australia. Participants 39 patients and 80 family members who were involved in high severity healthcare incidents (leading to death, permanent disability, or long term harm) and incident disclosure. Recruitment was via national newspapers (43%), health services where the incidents occurred (28%), two internet marketing companies (27%), and consumer organisations (2%). Main outcome measures Participants’ recurrent experiences and concerns expressed in interviews. Results Most patients and family members felt that the health service incident disclosure rarely met their needs and expectations. They expected better preparation for incident disclosure, more shared dialogue about what went wrong, more follow-up support, input into when the time was ripe for closure, and more information about subsequent improvement in process. This analysis provided the basis for the formulation of a set of principles of effective incident disclosure. Conclusions Despite growing prominence of open disclosure, discussion about healthcare incidents still falls short of patient and family member expectations. Healthcare organisations and providers should strengthen their efforts to meet patients’ (and family members’) needs and expectations.